2012
DOI: 10.1371/journal.pone.0035620
|View full text |Cite
|
Sign up to set email alerts
|

Natural DNA Uptake by Escherichia coli

Abstract: Escherichia coli has homologues of the competence genes other species use for DNA uptake and processing, but natural competence and transformation have never been detected. Although we previously showed that these genes are induced by the competence regulator Sxy as in other gamma-proteobacteria, no conditions are known that naturally induce sxy expression. We have now tested whether the competence gene homologues encode a functional DNA uptake machinery and whether DNA uptake leads to recombination, by invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…A number of pathogens harboring T4P, including Pseudomonas aeruginosa and enterohemorrhagic E. coli (EHEC), are highly suspicious of being competent given the excessive HGT documented for their genomes, but to date they have not been shown to undergo transformation naturally (55)(56)(57). Our finding that the comEC mutants are attenuated in the Galleria mellonella infection model while the pilT mutants are not is unexpected.…”
Section: Discussionmentioning
confidence: 72%
“…A number of pathogens harboring T4P, including Pseudomonas aeruginosa and enterohemorrhagic E. coli (EHEC), are highly suspicious of being competent given the excessive HGT documented for their genomes, but to date they have not been shown to undergo transformation naturally (55)(56)(57). Our finding that the comEC mutants are attenuated in the Galleria mellonella infection model while the pilT mutants are not is unexpected.…”
Section: Discussionmentioning
confidence: 72%
“…has shown that competence induction also depends on quorum sensing, pyrimidine precursors, and the presence of chitin breakdown products generated from crustacean exoskeletons (38)(39)(40)(41)(42). Although Escherichia coli's competence gene homologs enable cells to use DNA as a sole source of carbon, attempts to demonstrate natural competence in E. coli have not been successful (43,44). Less is known about regulatory mechanisms in other Gram-negative species, since culture conditions that induce competence have not been linked to specific regulators (4,45).…”
Section: The Mechanism and Function Of Natural Competencementioning
confidence: 99%
“…antibiotics. E. coli is one of the Gram-negative bacteria that is naturally competent for transformation [43,44], but the competence is time limited [45]. Again, a longer contact time will increase the probability of uptake.…”
Section: Antibiotic Resistance Induction In Wwtpmentioning
confidence: 99%